2020
DOI: 10.1186/s43141-020-00083-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the genes involved in the ethylene biosynthesis pathway in Arabidopsis thaliana and Oryza sativa

Abstract: Background Ethylene is a gaseous plant hormone that acts as a requisite role in many aspects of the plant life cycle, and it is also a regulator of plant responses to abiotic and biotic stresses. In this study, we attempt to provide comprehensive information through analyses of existing data using bioinformatics tools to compare the identified ethylene biosynthesis genes between Arabidopsis (as dicotyledonous) and rice (as monocotyledonous). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 121 publications
1
23
0
Order By: Relevance
“…Glycosylation modifications may change the stability and molecular weight of the target protein [73,74]. In addition, phosphorylation modifications play critical roles in protein activity, protein-protein interactions, and the regulation of signal transduction [65,75,76]. Previous studies have revealed that posttranslational modifications such as phosphorylation are involved in activating the K+ channel AKT1 [1,21,31].…”
Section: Discussionmentioning
confidence: 99%
“…Glycosylation modifications may change the stability and molecular weight of the target protein [73,74]. In addition, phosphorylation modifications play critical roles in protein activity, protein-protein interactions, and the regulation of signal transduction [65,75,76]. Previous studies have revealed that posttranslational modifications such as phosphorylation are involved in activating the K+ channel AKT1 [1,21,31].…”
Section: Discussionmentioning
confidence: 99%
“…The recognized genes were belonged to ,PHT2,PHT4,PHO1,PHO1 homologs,inorganic PHTs, xylulose 5-PHTs, glucose-6-phosphate translocators, and phosphoenolpyruvate translocators. Regarding the physicochemical properties, the PHT proteins were stated with high diversity in terms of pI, molecular weight, GRAVY value, and exon number, indicating that these transporter genes may be associated with various cellular pathways (Ahmadizadeh et al, 2020a(Ahmadizadeh et al, , 2020b. Interestingly, all PHO1 homolog proteins were showed a negative GRAVY value, revealing that the PHO1 homolog proteins are hydrophilic (Heidari et al, 2019;Rezaee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Post-translation modifications such as phosphorylation processes cause significant effects on protein activities and inducing cell signaling (Heidari et al, 2020a;Silva-Sanchez et al, 2015). The high phosphorylation potential of PHO1 proteins may indicate that these proteins are involved in various cellular processes under signal transduction pathways (Ahmadizadeh et al, 2020a). Regarding the promoter region analysis, various cis-acting elements associated with response to stress conditions and phytohormones were found in the upstream region of PHT genes.…”
Section: Discussionmentioning
confidence: 99%
“…Magnesium transporters as well as other ion transporters are not only involved in response to Mg concentrations, but also their activity can be affected by changes in environmental conditions [10,12]. Analysis of gene promoter regions is one of the strategies to predict the response of target genes to various environmental factors [77,78]. MGT genes have a high potential to respond to stresses, both biotic and abiotic, as well as ABA based on the distribution of corresponding cis-regulatory elements in the promoter region.…”
Section: Discussionmentioning
confidence: 99%